2013
DOI: 10.1089/tmj.2012.0087
|View full text |Cite
|
Sign up to set email alerts
|

Teledentistry: Distant Diagnosis of Oral Disease Using E-Mails

Abstract: Objective: The purpose of this study was to evaluate the applicability of telediagnosis in oral medicine, through the transmission of clinical digital images by e-mail. Subjects and Methods: The sample included 60 consecutive patients who sought oral medicine services at the Federal University of Parana´, in the state of Parana´, located in southern Brazil. The clinical history and oral lesion images were recorded using clinical electronic charts and a digital camera, respectively, and sent by e-mail to two or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
42
2
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 18 publications
4
42
2
6
Order By: Relevance
“…Interestingly, there was a high level of concordance between the opinion of applicants and specialized oral medicine teleconsultants. This finding is in accordance with previous studies (Petruzzi & De Benedittis, ; Torres‐Pereira et al., ). Nevertheless, it should be noted that only a few professionals informed a clinical impression.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Interestingly, there was a high level of concordance between the opinion of applicants and specialized oral medicine teleconsultants. This finding is in accordance with previous studies (Petruzzi & De Benedittis, ; Torres‐Pereira et al., ). Nevertheless, it should be noted that only a few professionals informed a clinical impression.…”
Section: Discussionsupporting
confidence: 94%
“…In a previous study, Torres‐Pereira et al. () demonstrated that in 88% of cases, one of two remote consultants was capable of providing the right diagnosis when compared with the gold standard. Another question to be explored would be the impact of this kind of service on the efficacy of public health services.…”
Section: Discussionmentioning
confidence: 99%
“…Besides its use for identifying TDIs, the development of TD has allowed remote diagnoses in different dental specialties, such as Oral Pathology, Stomatology, and Pediatric Dentistry through examinations of digital images . It is also possible to share radiographic images, increasing the chances of a correct diagnosis .…”
Section: Discussionmentioning
confidence: 99%
“…Photographs may also be very useful in research and to furnish key pieces of evidence in legal proceedings. 27 In studies that have aimed to validate TD tools, the use of digital photographs for the diagnosis of caries lesions [28][29][30] and oral lesions 31,32 was confirmed as a reliable alternative.…”
mentioning
confidence: 99%
“…Even though face-to-face encounters between health professionals and patients remain the gold standard for patient evaluation in all medical fields, telediagnosis is a useful alternative when the availability of specialized care is limited [8]. Taking this into account, TelessaúdeRS-UFRGS, a major university-based telehealth program in Brazil [9], has created EstomatoNet, a teledentistry service available free of charge to PHC physicians and dentists in the state of Rio Grande do Sul to enhance care, prevent unnecessary referrals to specialists, and decrease the time between referral and specialty consultations [10].…”
Section: Telediagnosis As a Tool To Enhance Access To Specialized Carementioning
confidence: 99%